APPRAISING INDIA’S ROLE IN UNITED NATIONS PEACE KEEPING OPERATION IN AFRICA: THE CASE OF SOUTH SUDAN - Omede, Jolade Omede; Ngwube, Arinze; Idowu, Aluko Opeyemi (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
India has long invested in promoting goodwill among African states by participating in United Nations Peacekeeping operations. India is the third-largest contributor of personnel to UN peacekeeping operations and has contributed to various missions across the world including in Somalia, Mozambique, Angola, Sierra Leone, and more recently, the Democratic Republic of Congo and South Sudan. As part of a broader push to build stronger ties to African countries, India has redoubled its commitment to peacekeeping efforts over the past decade, and in the views of many in the UN peacekeeping system, the capacity of Indian peacekeepers makes them essential to any peacekeeping effort on the continent. India also possesses the capacity to provide well-trained troops who are accustomed to operating in a diverse array of terrain. In addition, the paper will assess India’s strategy of using peacekeeping as a tool of foreign policy. This paper will assess the role of India in the South Sudan Crisis. The paper’s source of data will be essentially secondary involving books, journals; articles on the subject matter under review.